BOOST YOUR PASSIVE INCOME BY BECOMING STOCKPRENEURIN CAPITAL MARKET - Setiyadi, Teguh; Rahmaniah, Fairdauzi Aulia (Majalah Ilmiah Inspiratif, 2023)
The desire to increase passive income as an alternative to obtain returns inaddition to the main income from active income, also considering the increasingnumber of trading platforms on various social media, encourages us as students of theManagement Study Program, Pandanaran University, Semarang, who have indeedbeeninvolved in the world of passive income for some time to hold a national seminar oncapital markets in more depth for other students who are included in the millennial generation to better understand the world of capital markets and understand howtomake safe passive income investments, especially stock investments by minimizingthelevel of risk that will be faced when investing and making choices to determine asafetrading platform according to the conditions of the investor. There needs to be an introduction to the capital market as early as possible forthe millennial generation, or the general public. In this introduction, students of theManagement Study Program at Pandanaran University in collaboration with IDXhelda national seminar entitled "Boost Your Passive Income by Becoming Stockpreneur inCapital Market". This national seminar on the capital market can be a guide formillennials to become Stockpreneurs or Stock Entrepreneurs. The purpose of holdingthis national seminar is to invite young people to start preparing themselves in formingan entrepreneurial spirit and increasing passive income in the present, as well asdeveloping knowledge about how to make safe transactions in the capital market, sothat in the future they can become stockpreneurs. Keywords: passive income, stock investment and capital market